Fundamentals Of Bioinformatics - Irfan Ali Khan Atiya Khanum (Ukaaz Publications, 2003)
Computers are now an integral part of the Biological world and without them, advancements in Biology and Medicine would undoubtedly be hindered. The partnership between these non-living structures (computers) and biology has created a need for mergers in certain aspects of the computational and biological sciences. Computer Science in medicine and computational biology allow for faster analysis of biological data and the Discovery of many previously unknown biological trends. These trends, in turn, have been instrumental in therapeutic advancements (eg. Drug design) in prolonging and enhancing life expectancy across the globe. Sensing the importance, articles of this book have been compiled to give a clear cut Picture on the subject, and also help the Medical practitioners to keep abreast of the latest developments.